Assessing impulsivity: Relationships between behavioral and self-report measures in individuals with and without self-reported ADHD. (1st February 2017) - Barnhart, Wesley R.; Buelow, Melissa T.
Abstract: The present study examined relationships between self-report and behavioral measures of impulsivity, a personality characteristic linked to diagnostic criteria for multiple psychological disorders, in individuals who either self-reported ( n  = 28) or did not self-report ( n  = 147) a history of Attention-Deficit/Hyperactivity Disorder (ADHD) diagnosis. Undergraduate student participants completed several self-report measures of impulsivity (Barratt Impulsiveness Scale, Impulsive Sensation Seeking subscale, BIS/BAS Scale, Conner's Adult ADHD Rating Scale, and Frontal Systems Behavior Rating Scale) and three behavioral measures of impulsivity (Balloon Analogue Risk Task, Delay Discounting Task, Stroop). A principal components analysis indicated three components encompassing attentional impulsiveness, reward sensitivity, and behavioral and motor impulsiveness; however, none of the behavioral measures factored with the self-report measures. Logistic regressions found attentional impulsiveness to distinguish between individuals with and without a self-reported history of ADHD diagnosis. Impulsivity is a multi-faceted construct, and the utilization of multiple measures, both self-report and behavioral, can aid to more fully and accurately assess the construct in both research and clinical settings. Highlights: Impulsivity has no uniform definition across clinical and non-clinical studies. The present study examined self-report and behavioral measures of impulsivity. Participants with and without self-reported history of ADHD completed an assessment. Three factors of impulsivity emerged on a principal component's analysis. Attentional impulsivity differentiated between individuals with and without a history of self-reported ADHD diagnosis.